The challenge of nonunion and malunion in distal femur surgical revision - Giuseppe Rollo; Paolo Pichierri; Predrag Grubor; Antonio Marsilio; Michele Bisaccia; Milan Grubor; Valerio Pace; Riccardo Maria Lanzetti; Marco Giaracuni; Marco Filipponi; Luigi Meccariello (Medicinski glasnik, 2019)
Aim: To demonstrate validity of a bio-metallic solution in bone healing combined with the quadriceps safe approach in the treatment of nonunions of distal femur while malunions were treated by metallic solution. Methods: We treated 57 patients with nonunion or malunion of distal femur at the Orthopaedics and Traumatology Department of a single orthopaedic trauma centre (Italy). A total of 57 patients were divided in two groups: the first (NU) group was composed of 35 patients affected; the second group (MU) was composed of 22 patients affected by malunion of distal femur. Criteria chosen to evaluate the two groups during a clinical and radiological followup were: the quality of life measured by the Short Form (12) Health Survey, the knee function and quality of life related to it measured by the Knee Injury and Osteoarthritis Outcome Score KOOS and the Knee Society Score, bone healing measured by modified Radiographic Union Score by X-rays during the follow-up and CT at one year after the surgery, the difference of the limbs length before and after the revision surgery, and postoperative complications. The evaluation endpoint was set at 12 months. Results: There were no statistical differences between the two groups. Conclusion: The role of bio-metallic solution in the treatment of nonunions and malunions is to recreate the knee anatomy and functionality compatible with a satisfactory quality of life.
Keywords: femoral fractures; internal fracture fixation; malunited fracture; nonunited fracture; revision surgery